Potential application of natural coagulant extraction from walnut seeds for water turbidity removal. Issue 3 (23rd February 2022) - Zedan, Tariq; Mossad, Mohamed; Fouad, Moharram; Mahanna, Hani
Abstract: In this study, natural coagulant obtained from walnut seeds was used in water treatment for the removal of turbidity as a coagulant and as a coagulant aid with alum. The study was conducted by using a jar test under various operational parameters. The tests were carried out with initial turbidity of 10–200 NTU, pH of 3–11, and natural coagulant dose of 1–5 ml/L. The characterization of walnut natural coagulant was carried out using SEM, FTIR, EDX, and zeta potential analyzer. The coagulation activity and turbidity removal efficiency were evaluated for each run. The optimum dose of the walnut seed extract may be found to be 3 ml/L. The highest turbidity removal efficiency was achieved at pH above 7. Walnut seed extract used as coagulant and with alum was able to enhance coagulation process performance and decrease the alum dose required for the coagulation process performance and decrease the alum dose required for the coagulation process. Walnut seed extract has a negligible impact on organic matter content in the coagulated water. Furthermore, ANNs model of turbidity removal using walnut seed extract was conducted and yielded a high coefficient of determination (R 2 of 0.96). HIGHLIGHTS: Walnut seeds extract is an efficient coagulant for water turbidity removal. Walnut seeds extract could be used as a coagulant aid with alum. The highest turbidity removal efficiency was achieved at pH above 7. Walnut seed extract has a negligible impact on organic matter content in the coagulated water. ANNs model of turbidity removal using walnut seed extract yielded a high coefficient of determination (R2 of 0.96). Graphical Abstract